Carboxylated Cellulose Nanocrystals in Semi-Interpenetrated Network Hydrogels and Its Application in Water Absorption and Antibiotic Removal - Bruna-Bugueno, J; Santander-Meyer, R; Roa-Ruiz, K; Salfate-Calderon, G; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2025)
The water scarcity crisis is currently deepened by the presence of emerging contaminants, such as amoxicillin (AMX), threatening ecosystems and living beings due to their toxicity and bioaccumulation. Due to this, in the present study, superabsorbent hydrogels reinforced with oxidized cellulose nanocrystals (CCNC) were developed, forming semi-interpenetrated networks with poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS). The CCNCs were obtained by acid hydrolysis and subsequent chemical oxidation to introduce carboxylate groups with two different levels (low and high) of 200 mmol kg-1 (L-CCNC) and 677 mmol kg-1 (H-CCNC), respectively. The effective oxidation of the crystals was confirmed by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and X-ray diffraction, where this reaction did not affect their crystallinity, but reduced their thermal stability. While the obtained hydrogels were characterized chemically, thermally, morphologically and mechanically by FTIR, TGA, scanning electron microscopy, hydration and dynamic compression tests. The incorporation of CCNC to PAMPS increased the thermal stability and modified the surface area of the hydrogels. In addition, the maximum hydration capacity reached 4900 % for PAMPS hydrogels with 10 % H-CCNC, maintaining greater flexibility under compression. Finally, in AMX adsorption studies, parameters such as pH, contact time, initial AMX concentration and amount of adsorbent were evaluated. Achieving a maximum adsorption capacity of 136 mg g-1 with the possibility of reuse in three consecutive adsorption-desorption cycles. These findings highlight the potential of superabsorbent hydrogels reinforced with CCNC as sustainable materials for environmental applications. © 2025 Elsevier B.V.